RESEARCH PRODUCTIVITY OF BI-MONTHLY JOURNAL OF ANIMAL RESEARCH DURING 2013 – 2020: A SCIENTOMETRIC APPRAISED - L., Rajendran (International Journal of Research -GRANTHAALAYAH, 2021)
Animal research from the bimonthly Journal of Animal Research was collected using scientometric analysis from 2013 to 2020. According to the study, 1057 publications were written between 2013 and 2020, with 48 of them having a high publication rate in 2015. As a result, animal research is the most popular topic among veterinary researchers, with 1164 papers published out of 1057 submitted. During the years, author R.K.Sharma published 22 articles, while other authors published (2,3,4,5,6,7,8,9,10,11,12,14,17,19,21) articles (2013 to 2020).